2013
DOI: 10.1021/ie301580m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Physical Properties and Process Conditions on Entrainment Behavior in a Static-Mixer Settler Setup

Abstract: This paper examines the role of physical properties (interfacial tension, the viscosity of the dispersed and continuous phase, density difference, and solubility), and process conditions (flow rate, phase ratio, and temperature) on the drop size and entrainment in a static-mixer settler setup. Two extraction systems were investigated, that is, caprolactam–toluene–water and ethylbenzene (EB)−α-methyl benzyl alcohol (MBA)–water/NaOH (pH = 12). Depending on the system, the entrainment increased by a factor of 5–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Figure 5 a) shows the effect of the energy dissipation on d32 for different dispersed phase fractions while Figure 5 b) shows the effect of the energy dissipation on d32 for different oil viscosities. In accordance with the literature (Barega et al, 2013;Das et al, 2013;Theron et al, 2010), both figures show that increasing ϵ (or the velocity or the Reynolds number) induces a slight decrease in d32 due to the increase in the level of turbulence involving higher inertial forces and pressure gradients. However, d32 is constant above hydraulic ϵ= 1000 W kg -1 , which could be explained by a balance between breakup and coalescence mechanisms.…”
Section: Influence Of the Hydrodynamic Parametersupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 5 a) shows the effect of the energy dissipation on d32 for different dispersed phase fractions while Figure 5 b) shows the effect of the energy dissipation on d32 for different oil viscosities. In accordance with the literature (Barega et al, 2013;Das et al, 2013;Theron et al, 2010), both figures show that increasing ϵ (or the velocity or the Reynolds number) induces a slight decrease in d32 due to the increase in the level of turbulence involving higher inertial forces and pressure gradients. However, d32 is constant above hydraulic ϵ= 1000 W kg -1 , which could be explained by a balance between breakup and coalescence mechanisms.…”
Section: Influence Of the Hydrodynamic Parametersupporting
confidence: 91%
“…The superficial velocity was also directly considered as a driving force for breakup (Barega et al, 2013):…”
Section: Correlations For the Drop Size In Turbulent Flowmentioning
confidence: 99%
“…It has to be stable enough to prevent from coalescence and destabilization in course of polymerization. Different continuous processes are available to create liquid-liquid dispersion including membrane [13], rotor-stator [14], static mixer [15][16][17], colloid mills [14,18], high pressure homogenizer [19], mixer-settler [20] and pulsed column [21,22]. A remarkable feature of continuous liquid-liquid dispersion processes are their ability to create quickly droplet of controlled size.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the nonNewtonian fluid flow requires a shorter length to develop than the Newtonian fluid. The above mentioned papers and others (Barega et al, 2013;Jin and Cheng, 2011), confirm that the static mixer, when compared with a conventional impeller, can yield a more controlled and scalable rate of dilution in fed batch system and also homogenize feed streams with a minimum residence time with less power consumption.…”
Section: Introductionmentioning
confidence: 76%